Eu falo, tu hablas, vos hablás, nós ensinamos e aprendemos juntos: aulas de línguas em cursos binacionais - Citolin, Cristina Bohn (Universidade do Vale do Rio dos Sinos, 2013)
The present research was realized within the first technical binational courses offered by the Brazilian Technologic and Professional Federal Network, in partnership with Consejo de Educación Técnico Profesional – Universidad Del Trabajo Del Uruguay, in Uruguay. The aim of the research was to analyze and discuss data about one of the interfaces of this pilot-project of Brazilian Ministery of Education, sponsored by SETEC/MEC, in the border between both countries: the teaching of language. The thoughts orient by the following research question: “What conceptions, practices and knowledges are being built and in action in the learning and teaching of language in binational courses, in the border between Brazil and Uruguay?”. The methodology used the triangulation of data from semi-structured interviews, documental analysis and recording the binational meetings, treated with theoretical-methodological approach of Content Analysis. The subjects of this study are six professors of language, Brazilian and Uruguayan, and a manager. Data revealed that there are significant learning built through docent action in this context, specially by the shared teaching process. The collective and collaborative work is identified as a strengthener of relations among professors, of docent formation and the construction of educative processes that reach good results. There is approximation of language conceptions and docent teaching orientated to the recognizing of border’s culture, identity and linguistic variety. Authors as Sturza (2005, 2006), Behares (2010), Bagno (2005, 2006, 2007), Cunha (2010) e Tardif (2002) compose the theoretical referential. n
Keywords: Docência compartilhada; Ensino de línguas; Fronteira; Turmas bilíngues; Formação continuada; Shared teaching; Language education; Frontier; Bilingual classes; Continuing formation; ACCNPQ::Ciências Humanas::Educação